The Promise and Limitations of Student Belonging as a Predictor of Retention - David Gilani; Daniel McArthur; Liz Thomas (Trends in Higher Education)
Efforts to improve student retention are regularly explored within higher education literature and practice due to their status as a noble aim shared by governments, universities, and students themselves. To this end, students’ sense of belonging has become an increasingly popular topic of study due to its comprehensive links to student success. However, while student retention is understood as a binary, externally defined metric, student belonging is subjective, messy, and dynamic. This study utilises a longitudinal design to explore the changing relationship between student belonging, intention to persist, and eventual continuation with 101 first-year undergraduate students at two English universities. Regression analyses were utilised to build on previous research showing the near-perfect correlation between belonging and students’ intention to persist. Sense of belonging was also a strong predictor of eventual continuation status for all time-point measures of belonging except at the start of the first academic year. These findings provide further evidence for the promise of student belonging as a tool for practitioners to pre-empt risks of withdrawal. However, the findings also suggest that early measurements of a sense of belonging could be less reliable.